2012
DOI: 10.1258/ijsa.2011.011213
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence among men who have sex with men in New Zealand 1985–2009: 25 years of public health monitoring

Abstract: Annual population-based estimates of the number of men who have sex with men (MSM) with diagnosed HIV infection (HIV prevalence pool), and the proportion of all MSM this represents (HIV prevalence), have been insufficiently described over the long term. We investigated the dynamic effects of ongoing HIV diagnoses, lower mortality due to treatment and growth in the MSM population over time on these two epidemic indicators using national HIV/AIDS surveillance data in New Zealand, 1985-2009. The diagnosed HIV pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The stable proportion of respondents with diagnosed HIV infection is consistent with estimates of diagnosed HIV prevalence among MSM from national surveillance1 and from sexual health clinics 6. This is in contrast to a rising number of MSM living with diagnosed HIV,1 many of whom will now be ageing.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The stable proportion of respondents with diagnosed HIV infection is consistent with estimates of diagnosed HIV prevalence among MSM from national surveillance1 and from sexual health clinics 6. This is in contrast to a rising number of MSM living with diagnosed HIV,1 many of whom will now be ageing.…”
Section: Discussionsupporting
confidence: 71%
“…This is in contrast to a rising number of MSM living with diagnosed HIV,1 many of whom will now be ageing. As behavioural surveys will oversample younger gay community members, a stable diagnosed HIV prevalence is an indication of ongoing incidence, reduced mortality due to antiretroviral therapy (ART) and retirement from the sexually active population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As with virtually all studies on MSM, the absence of census data on sexual orientation means that the representativeness of this sample cannot be traditionally assessed [49]. In 2008, the New Zealand resident male population aged 15-59 was 1,290,600; assuming a 2% prevalence of same-sex behaviour this enumerates 25,812 MSM [14], approximately 45% of whom live in Auckland [49]. We believe our sample represents a broad cross-section of YMSM who participate in both social and sexual community settings in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…One concern is that MSM with undiagnosed HIV [11], particularly soon after acquisition and consequently not on treatment, account for a disproportionate fraction of new infections; Australian research suggested that 31% of new HIV infections occur from the estimated 9% of MSM with undiagnosed HIV in Australia [12]. In New Zealand, as in many other developed countries, the HIV epidemic continues to predominantly affect MSM [13,14]. A recent community survey in Auckland (New Zealand’s largest city) found that 21% of HIV-infected MSM were undiagnosed [15], suggesting that the proportion of new infections attributable to this group is likely considerable.…”
Section: Introductionmentioning
confidence: 99%